Pengaruh Kebijakan Kepala Sekolah, Dukungan Guru dan Implementasi Pembelajaran Berdiferensiasi Terhadap Prestasi Belajar Siswa - Tajuddin Tajuddin; Muh. Yunus; Rego Devila (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze the influence of principal's policy, teacher support, and implementation of differentiated learning on the learning achievement of grade XI students at SMAN 2 Kepulauan Selayar. The study used a quantitative explanatory approach with multiple linear regression analysis. The research sample consisted of 80 students selected through purposive sampling. Data were collected through questionnaires, observation, and documentation, then analyzed through prerequisite tests, t-tests, F-tests, and coefficients of determination. The regression equation obtained was Y = 54.230 + 1.909X1 + 2.612X2 + 2.339X3. Principal's policy had a positive and significant effect on learning achievement (t = 4.612; p < 0.001). Teacher support also had a positive and significant effect (t = 5.963; p < 0.001). The implementation of differentiated learning had a positive and significant effect (t = 5.730; p < 0.001). The simultaneous test showed that the three variables had a significant effect on learning achievement (F = 26.100; p < 0.001), with an R Square of 0.507.